The Logic of Creativity. - Blanco‐Pérez, Carlos (Heythrop Journal, 2020)
The article focuses on the nature of creativity can be addressed from disciplines as varied as neuroscience, psychology and philosophy. Topics include that creativity is probably the most enigmatic concept of the human mind; mentions that lack of ideas paralyzes scientific progress and social development; and also mentions that within a biological framework, creativity can be regarded as the foremost manifestation of adaptability.